An American engineer in China - Parsons, William Barclay 1859-1932 (Cambridge library collection. Technology, 2013)
By the late 19th century, twenty-nine Chinese ports were open for foreign trade. Often run by foreign commissioners and no longer subject to the stringent local laws, these ports levied one of the smallest import taxes in the world, and Chinese commerce exploded. Originally published in 1900, this account by William Barclay Parsons (1859-1932) investigates the ensuing surge of economic and industrial development in the eastern provinces. Including an introduction to China's history and the structure of its civil service, the book analyses the corrupt but ingenious world of customs officials, the importance of American cotton interests, and export statistics which reveal the huge smuggling operations that slipped around official embargoes. Set against a backdrop of electric lights and western labels in even the most closed of cities, this shows the early stages of today's global market.